If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -2(x + -1) = 4 + -1x Reorder the terms: 5 + -2(-1 + x) = 4 + -1x 5 + (-1 * -2 + x * -2) = 4 + -1x 5 + (2 + -2x) = 4 + -1x Combine like terms: 5 + 2 = 7 7 + -2x = 4 + -1x Solving 7 + -2x = 4 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 7 + -2x + x = 4 + -1x + x Combine like terms: -2x + x = -1x 7 + -1x = 4 + -1x + x Combine like terms: -1x + x = 0 7 + -1x = 4 + 0 7 + -1x = 4 Add '-7' to each side of the equation. 7 + -7 + -1x = 4 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 4 + -7 -1x = 4 + -7 Combine like terms: 4 + -7 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3
| 5(3y-4)-3(2y+1)= | | x+(-47)=-37 | | 10x+15=12x-1 | | 52/12-17/10+3/4 | | 7x+3=30-2x | | 7/12k=I | | 3x-18=3*1 | | 7x+3=20-2x | | 2t^2+2t-2=0 | | 2(3x-4)+2=42 | | 2x-3=-20x | | 2x-3=-20 | | 2x-3=4*2 | | =15+273.15 | | 8000/4 | | X+(X*0.05)=1068 | | 5x+8=60-125x | | (2x-1)=3(x+7) | | 9x+7y+17z=107 | | 4-(15-2x)=3(2x-9-2(9-x)) | | 4x^2-3x+12=0 | | 60x+1=3(3+4x) | | 60x+10=80x-6 | | 36=2l+2w | | -21=7+6(c+5) | | 10x+1=12x-17 | | -6(7-9x)=-21 | | 6.8x=18000+(2x) | | -3+6(1+9v)=-28 | | -270=-5(9x-9) | | x/-12+4=9 | | y/3+18=70 |